Caldora penicillata gen. nov., comb. nov. (Cyanobacteria), a pantropical marine species with biomedical relevance. Issue 4 (2nd July 2015) - Engene, Niclas; Tronholm, Ana; Salvador‐Reyes, Lilibeth A.; Luesch, Hendrik; Paul, Valerie J.; Gabrielson, P.
<x xml:space="preserve">Abstract</x> Many tropical marine cyanobacteria are prolific producers of bioactive secondary metabolites with ecological relevance and promising pharmaceutical applications. One species of chemically rich, tropical marine cyanobacteria that was previously identified as Symploca hydnoides or Symploca sp. corresponds to the traditional taxonomic definition of Phormidium penicillatum. In this study, we clarified the taxonomy of this biomedically and ecologically important cyanobacterium by comparing recently collected specimens with the original type material and the taxonomic description of P. penicillatum. Molecular phylogenetic analyses of the 16S rRNA gene and the 16S‐23S internal transcribed spacer regions showed that P. penicillatum formed an independent clade sister to the genus Symploca, and distantly related to Phormidium and Lyngbya. We propose the new genus Caldora for this clade, with Caldora penicillata comb. nov. as the type species and designate as the epitype the recently collected strain FK13‐1. Furthermore, the production of bioactive secondary metabolites among various geographically dispersed collections of C. penicillata showed that this species consistently produced the metabolite dolastatin 10 and/or the related compound symplostatin 1, which appear to be robust autapomorphic characters and chemotaxonomic markers for this taxon.